Gender Equality in Islamic Inheritance Law: Rereading Muhammad Shahrur’s Thought - Ridwan (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
This article shows that the spirit of Islamic inheritance law is justice focusing on the sociological and gender roles of a man and woman in the accumulation of property on their gender role. The difference in the portion of legacy is not determined by sex. Shahrur’s gender responsive-reading of inheritance law text cannot be separated from its historical root and is always discussed with the current social context. Legacy distribution is based on female heirs’ position, while men’s portion adapts to the existence of female heirs, besides the kinship factor. Shahrur’s idea with the theory of hudud is offered to be an alternative model of Indonesian inheritance law reform.